Racial Disparities in Federal Sentencing Outcomes: Clarifying the Role of Criminal History - Franklin, Travis William (Crime & delinquency, 2020)
Racial and ethnic sentencing disparities are frequently conditioned by offender and case characteristics (e.g., gender, crime type). Offenders' criminal history is a potentially important conditioning factor, yet this issue has only been addressed by a small body of research. Moreover, no study has examined this potential conditioning effect among Asian or Native American offenders, and prior research has typically adopted a limited theoretical approach for explaining why criminal history might condition racial disparities. The present study addresses these shortcomings in an analysis of United States Sentencing Commission data for fiscal years 2010-2012. Results indicate that race and ethnicity effects are conditioned by criminal history in important ways. Implications for theory, research, and practice are discussed.